DAG1 haploinsufficiency is associated with sporadic and familial isolated or pauci-symptomatic hyperCKemia - Traverso, Monica; Baratto, Serena; Iacomino, Michele; Di Duca, Marco; Panicucci, Chiara; Casalini, Sara; Grandis, Marina; Falace, Antonio; Torella, Annalaura; Picillo, Esther; Onore, Maria Elena; Politano, Luisa; et al. (European journal of human genetics : EJHG, 2024)
DAG1 encodes for dystroglycan, a key component of the dystrophin-glycoprotein complex (DGC) with a pivotal role in skeletal muscle function and maintenance. Biallelic loss-of-function DAG1 variants cause severe muscular dystrophy and muscle-eye-brain disease. A possible contribution of DAG1 deficiency to milder muscular phenotypes has been suggested. We investigated the genetic background of twelve subjects with persistent mild-to-severe hyperCKemia to dissect the role of DAG1 in this condition. Genetic testing was performed through exome sequencing (ES) or custom NGS panels including various genes involved in a spectrum of muscular disorders. Histopathological and Western blot analyses were performed on muscle biopsy samples obtained from three patients. We identified seven novel heterozygous truncating variants in DAG1 segregating with isolated or pauci-symptomatic hyperCKemia in all families. The variants were rare and predicted to lead to nonsense-mediated mRNA decay or the formation of a truncated transcript. In four cases, DAG1 variants were inherited from similarly affected parents. Histopathological analysis revealed a decreased expression of dystroglycan subunits and Western blot confirmed a significantly reduced expression of beta-dystroglycan in muscle samples. This study supports the pathogenic role of DAG1 haploinsufficiency in isolated or pauci-symptomatic hyperCKemia, with implications for clinical management and genetic counseling.